In Addition to Poor Glycemic Control, a High Level of Irisin in the Plasma Portends Early Cognitive Deficits Clinically in Chinese Patients With Type 2 Diabetes Mellitus - Lin, Hongyan; Yuan, Yang; Tian, Sai; Han, Jing; Huang, Rong; Guo, Dan; Wang, Jiaqi; An, Ke; Wang, Shaohua (Frontiers in Endocrinology, 2019)
Background and objectives: Irisin plays an important role in the metabolism and homeostasis of energy balance, which is involved in cognitive impairment. This study aimed to investigate the role of irisin in mild cognitive impairment (MCI) among Chinese patients with type 2 diabetes mellitus (T2DM). Methods: We recruited 133 Chinese patients with T2DM, and divided them according to the Montreal Cognitive Assessment score. Demographic data were collected and the level of irisin in the plasma was determined. In addition, the results of neuropsychological testing were examined. The concentration of irisin in the plasma was measured using an enzyme immunoassay. Results: A total of 59 patients were diagnosed with MCI and 74 patients were included as healthy-cognition controls. The level of irisin in the plasma (p=0.043) and homeostasis model of assessment for insulin resistance (p=0.032) in diabetic patients with MCI were higher than those observed in the healthy controls. A higher level of irisin in the plasma was associated with impaired overall cognition, specifically executive function. Linear regression analysis suggested that irisin (p=0.017) and glycosylated hemoglobin (p=0.036) were independent factors of diabetic MCI. Conclusions: The level of irisin in the plasma correlated with cognitive impairment in T2DM patients, particularly with executive function. These results further suggest that, in addition to poor glycemic control, a high level of irisin in the plasma portends early cognitive deficits clinically in Chinese patients with T2DM.